2023
DOI: 10.9734/ajarr/2023/v17i5482
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 5E Instructional Model on Students’ Performance in Mathematics Non-routine Problem

Abstract: The study's aim was to determine the impact of the 5E instructional model on students' performance in non-routine mathematics problems. The population was made up of junior high school students in Oforikrom municipality, Ghana's Ashanti Region. The study used a quasi-experimental non-equivalent design. A total of 84 students were drawn at random from Oforikrom's two Junior High Schools. The experimental and control groups were assigned at random to the two schools. The experimental group was taught using the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It increases conceptual understanding, problem-solving abilities, selfefficacy, and positive attitudes toward science. The relatively few studies done to implement the 5E in the teaching and learning of mathematics revealed that it promotes flexibility in mathematics instruction and results in increased student conceptual and procedural knowledge, mathematical reasoning and performance (Tuna and Kacar, 2013;Bakri, 2021;Adu and Folson, 2023;Pheaukkhai and Cheausuwantavee, 2023;Alabdulaziz, 2024).…”
Section: Science Inquirymentioning
confidence: 99%
“…It increases conceptual understanding, problem-solving abilities, selfefficacy, and positive attitudes toward science. The relatively few studies done to implement the 5E in the teaching and learning of mathematics revealed that it promotes flexibility in mathematics instruction and results in increased student conceptual and procedural knowledge, mathematical reasoning and performance (Tuna and Kacar, 2013;Bakri, 2021;Adu and Folson, 2023;Pheaukkhai and Cheausuwantavee, 2023;Alabdulaziz, 2024).…”
Section: Science Inquirymentioning
confidence: 99%